The Study of the Mechanical Strength of Epoxy as an E-glass Composite Adhesive for Unmanned Aircraft - Muzayadah, Nurul Lailatul; Satrio Nurtiasto, Taufiq (SPECTA Journal of Technology, 2023)
An unmanned aircraft (UAV) is an aircraft that does not require a crew on board in its operation. This type of aircraft is widely used as a remote monitoring tool such as monitoring disaster sites, monitoring plantation areas, monitoring forests to monitoring enemy areas carried out by the military. For this reason, a study of the adhesive strength required in the connection of unmanned aircraft is needed, such as ribs, spars, skins. From the results of this study, it was found that the mechanical strength of epoxy adhesives depends on several factors such as manufacturer, epoxy content, and operating temperature. The hypothesis of the strength of the epoxy experiment results used by Pustekbang LAPAN ranged from 2,400.4 + 190.6 to 9,664.2 + 1,769.6 psi at room temperature.